TIME AND COST ANALYSIS OF DHOHO KEDIRI AIRPORT ACCESS ROAD PROJECT USING EARNED VALUE METHOD - Pramadha, Ichsan Yanuansyah; Hanie Teki Tjendani; Budi Witjaksana (International Journal Science and Technology, 2024)
Delays in project completion are something that any project contractor must avoid. Because apart from having a negative effect on the credibility of the project contractor, delays in project completion also cause penalty costs to be borne by the contractor, so that the profits to be obtained are reduced.Earned Value Method. This method is used to determine project performance in terms of costs at one time, determine project performance in terms of schedule/time at one time, predict costs to complete the project after the evaluation time and predict the time to complete the project after the evaluation.By using this method in the Kediri airport access road construction project, it was found that the project was delayed from the plan. The ETC (estimate to complete) value obtained was the estimated budget value required for completion was IDR 17,470,510,292.77, while the EAC (estimate at complete) value obtained was the final total cost estimate. project is IDR 32,509,153,464.05. TE Value Results (Time Estimate) to complete the project to completion in 89 calendar days or 5 days later than the contract time of 84 calendar days.